Optimizing insect pest control and nitrogen fertilizing of the summer turnip rape (Brassica campestris sutiva) - Kurppa, Sirpa; Ollula, Antti (Agricultural and Food Science, 1993)
The need for pest control could not be decisively reduced by boosting the compensatory ability of the summer turnip rape with extra nitrogen fertilizer. The plant compensated the damage of the blossom beetle (Meligethes aenus F.) by producing additional axillary racemes, pods and seeds. The compensation, in plant stands with about 300 plants/m2, reached its maximum capacity with a nitrogen quantity of 90 - 110 kg/hectare and covered about 30% of the harvest loss inflicted by the large blossom beetle population. Only, when the blossom beetle population barely exceeded the control threshold (one beetle per plant at the early bud stage) harvest loss was fully compensated by the extra nitrogen. The damage inflicted by the flea beetles (Phyllolrela spp.) was better compensated, however, the importance of the preventive seed treatment became evident during dry and especially warm emergence periods, when the threshold of 30 holes per plant was exceeded. The use of extra nitrogen, above the moderate 70 - 90 kg/ha, was found to yield 400 kg per hectare at the most, with insecticides the yield increased maximally by more than 1000 kg per hectare. The moderate quantity of nitrogen was, also, sufficient to produce the best operating margin in the cultivation even in heavy mineral soils.